2000
DOI: 10.4049/jimmunol.165.6.3301
|View full text |Cite
|
Sign up to set email alerts
|

The B Subunit of Shiga Toxin Fused to a Tumor Antigen Elicits CTL and Targets Dendritic Cells to Allow MHC Class I-Restricted Presentation of Peptides Derived from Exogenous Antigens

Abstract: Immunization with peptide or recombinant proteins generally fails to elicit CTL, which are thought to play a key role in the control of virus-infected cells and tumor growth. In this study we show that the nontoxic B subunit of Shiga toxin fused to a tumor peptide derived from the mouse mastocytoma P815 can induce specific CTL in mice without the use of adjuvant. The Shiga B subunit acts as a vector rather than as an adjuvant, because coinjection of the tumor peptide and the B subunit as separate entities does… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
95
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 123 publications
(99 citation statements)
references
References 65 publications
2
95
0
Order By: Relevance
“…Thus immunization with CTB by transcutaneous route may be suitable to stimulate immune response to cutaneous tumors as well as microbial infection. In regard to the other microbial toxins, it has been reported that Shiga toxin B subunit fused to tumor peptide elicits antitumor immune response to P815 murine mastocytoma (10). Molecular mechanism of adjuvant property of rCTB is not understood completely although binding to GM 1 gangliosides is required for rCTB to act as an adjuvant (21).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus immunization with CTB by transcutaneous route may be suitable to stimulate immune response to cutaneous tumors as well as microbial infection. In regard to the other microbial toxins, it has been reported that Shiga toxin B subunit fused to tumor peptide elicits antitumor immune response to P815 murine mastocytoma (10). Molecular mechanism of adjuvant property of rCTB is not understood completely although binding to GM 1 gangliosides is required for rCTB to act as an adjuvant (21).…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic efficacy to the established Meth A tumor cells using DC immunization was also investigated. 10 6 Meth A tumor cells were injected subcutaneously into the shaved back of BALB/c mice on day 0. Splenic DC were pulsed with 1 µg/ml rCTB and Meth A tumor cell lysate on day 1 and day 2, respectively, as described above.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several vectors have been reported to have this ability, including toxins (43,44), the protein transduction domain from the HIV, TAT protein (45), and AntpHD (26). Their common attribute is their capacity to deliver peptides directly in the cytosol in a receptor-dependent manner for toxins (44) or following spontaneous crossing of cell membranes in the case of TAT (46) and AntpHD (47). They all differ from exogenous proteins in terms of their internalization mechanisms, which commonly use phagocytosis/endocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that STxB delivers exogenous peptides into the MHC class I and II pathways of human and mouse dendritic cells (DCs) and induces humoral and cell-mediated immune responses that protect mice from tumor growth [18][19][20][21][22]. Functional TAP and proteasome activities are required for STxB-induced MHC class I-restricted antigen presentation, strongly suggesting that STxB delivers exogenous antigenic proteins and peptides across membranes into the cytosolic compartment [19]. The mechanism and exact intracellular site of this membrane translocation event have not yet been identified, but intracellular trafficking studies on human monocyte-derived DCs suggested that the retrograde route might not be involved [23].…”
Section: Introductionmentioning
confidence: 99%